أثر تحرير التجارة الخارجية على الميزان التجاري للقطاع الزراعي في سورية خلال الفترة الممتدة بين عامي (2001-2010) - نعيم معتز; الحوري غزل أكرم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتمحور موضوع البحث بشكل أساسي حول آثار عملية تحرير التجارة الخارجية على الميزان التجاري للقطاع الزراعي في سورية، بعد إجراء دراسة تحليلية لواقع هذا القطاع، وذلك نظراً لأهميته ومكانته في الاقتصاد الوطني، ولدوره الفعال في الإنتاج والتشغيل ودفع عجلة النمو الاقتصادي، سيما أن الاقتصاد السوري يصنف من الاقتصاديات الزراعية بالدرجة الأولى. فقد اتخذت التوجهات الاقتصادية الجديدة والاتفاقيات الإقليمية والدولية بين سورية والأطراف المتعاقد معها، إجراءات عديدة لتتماشى مع معطيات تحرير التجارة الخارجية وفتح الأسواق، مما أثر بشكل كبير على القطاع الزراعي، فعلى الرغم من أنها أسهمت إلى حد كبير في زيادة حجم ومعدل نمو التجارة الزراعية السورية، إلا أن هذه الزيادة قد نجمت زيادة حجم المستوردات الزراعية بشكل فاق حجم الصادرات الزراعية، مما أوقع الميزان التجاري للقطاع الزراعي في حالة عجز، بعد أن حقق فوائض كبيرة لفترات طويلة سابقة. وقد استنتج من الدراسة أن عملية تحرير التجارة الخارجية في سورية قد حملت في بعض جوانبها آثاراً سلبية على القطاع الزراعي تجلت في عجز ميزانه التجاري، بدلاً من أن تكون حافزاً ودافعاً له ليأخذ دوره الريادي في الاقتصاد الوطني. The Theme Of this research mainly focuses on the effects of foreign trade liberalization on the trade balance for agricultural sector in Syria , after conducting an analytical study of the reality of this sector . And that’s due to its importance and its Stature in the national economy, and its effective role in production , labor , and drive economic growth , especially that the Syrian economy is classified in the agricultural economies. As the new economic trend, and regional conventions between Syria and other parties , and its accompanying procedures followed in order to cope with the foreign trade liberalization data and open markets , may significantly effected the agricultural sector. Where although it contributed to increase the size and rate of growth of Syrian agricultural trade, but this increase is caused by an increase in the volume of agricultural imports that exceeded the volume of agricultural exportrs, and that led to a defict in its balance, after it has achieved larg surpluses for long period. It was concluded from the study, that the process of foreign trade liberalization carried in some of its aspects, negative effects on the Syrian agricultural sector, inparticular the defict of its trare balance, instead of being great motivation , to take its pioneering role in economy.